Structure and Spectro-scopic Properties of Nickel(II) Dimethylxanthate - ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2018)
The structural and spectroscopic characterization of nickel(II) dimethyl xanthate is described. DFT calculations revealed that the isolated molecule of the complex may exist in two nearly degenerated conformers (cis and trans, with the methyl groups of the ligand molecules positioned the same side or in opposite sides of the molecule, respectively; see Figure). In the crystalline compound, only the trans conformer is present, with the individual molecules in the crystal exhibiting a slightly distorter geometry from the D2h symmet~ -y point group due to intermolecular interactions. DFT and TD-DFT calculations were also carried on in order to interpret and help achieving full spectral assignment of the infrared spectra of the crystal and of the UV-vis absorbance spectrum of the complex in CHCI3 solution. The latter revealed that metal to ligand charge transfer is relevant in determining the electronic properties of the studied complex. On the other hand, the IR data point to relatively weak intermolecular interactions in the solid material, since the intramolecular vibrational potential describing the vibrations of the isolated molecule appears to be only slightly affected by the intermolecular potential. This conclusion is also supported by the structural data, the calculated equilibrium geometry for the trans isolated conformer and that found for the molecules within the crystal being very similar. Nevertheless, it was possible to identify the most important intermolecular interactions present in the crystal of the complex as being of the S•••H type.